2011
DOI: 10.1002/ctpp.201000504
|View full text |Cite
|
Sign up to set email alerts
|

A One‐Dimensional Particle‐in‐Cell Model of Plasma Build‐Up in Vacuum Arcs

Abstract: Understanding the mechanism of plasma build-up in vacuum arcs is essential in many fields of physics. A onedimensional particle-in-cell computer simulation model is presented, which models the plasma developing from a field emitter tip under electrical breakdown conditions, taking into account the relevant physical phenomena. As a starting point, only an external electric field and an initial enhancement factor of the tip are assumed. General requirements for plasma formation have been identified and formulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 42 publications
(59 reference statements)
3
40
0
Order By: Relevance
“…However, these studies have always excluded the third possibility of an impact, namely the ''staccato'' mode, or ''shower'' of ions, in which instead of being packed in a single cluster, scattered ions are carrying the energy towards the surface, each behaving as a single ion, but with minutely small delay between the impacts. MD simulations of such ion ''showers'' give results very close to the experimentally observed ones [8], which strongly suggests that the side craters are formed by the ''ion shower''. Although mostly this damage comprises a large area of a solidified metal liquid, the craters seen aside from the main spot resemble greatly the craters from ion and cluster ion impacts (Fig.…”
Section: Introductionsupporting
confidence: 72%
“…However, these studies have always excluded the third possibility of an impact, namely the ''staccato'' mode, or ''shower'' of ions, in which instead of being packed in a single cluster, scattered ions are carrying the energy towards the surface, each behaving as a single ion, but with minutely small delay between the impacts. MD simulations of such ion ''showers'' give results very close to the experimentally observed ones [8], which strongly suggests that the side craters are formed by the ''ion shower''. Although mostly this damage comprises a large area of a solidified metal liquid, the craters seen aside from the main spot resemble greatly the craters from ion and cluster ion impacts (Fig.…”
Section: Introductionsupporting
confidence: 72%
“…32 The central result obtained from the PIC simulations is the formation of a sheath potential 41 close to the cathode surface, where under the given conditions the electric field is roughly ten times higher than the initial gradient between the cathode and anode. Over this field, positive Cu ions are accelerated toward the cathode surface, obtaining potential energies peaking around 8 keV, for the external electric field value of 500 MV/m.…”
Section: Resultsmentioning
confidence: 94%
“…A detailed description of the plasma simulation model and additional results of the time evolution of the plasma is presented in Ref. 32.…”
Section: B Simulationsmentioning
confidence: 99%
“…In the rarefied plasma transport processes, neutral particle diffusion have an impact on the movement of the ions and electrons, especially in the rarefied plasma flow of a cathodic vacuum arc [10], [11], where neutral particle collisions as well as chemical dissociation and recombination reactions have an important role in the distribution of the charged particles during the diffusion process. The main numerical simulation DSMC/PIC method is currently used to solve such plasma transport problems in a rarefied environment [2], [3], [6]- [8], [10]- [12]. The PIC method can simulate the movement of charged particles in a self-consistent electrostatic field, and the DSMC method can be implemented to simulate the particle movement and collisions between neutral particles as well as charged particles.…”
mentioning
confidence: 99%
“…The DSMC/PIC method combines the advantages of the DSMC and PIC methods, and this method can be used to describe some other complex physical phenomena in the plasma arc jet flow. Timko et al [10] have investigated the one-dimensional plasma build-up in vacuum arcs by employing the PIC method, and it is shown that the evaporation of the neutral particles from the field emitter tip is the key factor in the arc development under vacuum conditions. Moore et al [13] have employed the DSMC/PIC method to study the breakdown in various microscale electrode gaps under an atmospheric pressure.…”
mentioning
confidence: 99%